Penerapan Metode Peer Tutoring untuk Meningkatkan Pemahaman Konsep Materi Perkalian Bersusun Pada Siswa Kelas III SD - Jhon Tetiwar; Oce Datu Appulembang (Program Studi Pendidikan Guru Sekolah Dasar, Universitas Kristen Satya Wacana, 2018)
In learning Mathematics, conceptual understanding is a primary competency that the students must acquire, because through understanding the concept the students would understand what is being learned and are able to apply them thus they can pursue toward the next materials. However, in the reality of a learning process, the students have not yet understood the concept correctly. Therefore, the researcher tried to implement the peer tutoring method. Thus this research is aimed to know that the implementation of peer tutoring method can improve the conceptual understanding on multiple multiplication of the grade III B students in SDN Inpres Harapan. The research method used in this research was Classroom Action Research methodology (CAR) of Kemmis and Taggart spiral model. This research was conducted upon the students of grade III B in SDN Inpres Harapan on August 2017 until October 2017 within three cycles. Instruments used in this research were teacher mentor observation sheet, teacher mentor and peer teacher interview sheet, students’ questionnaire, as well as students’ comprehension test sheet. Based on the research result, it can be concluded that the implementation of peer tutoring method can improve the conceptual understanding on multiple multiplication of the grade III B students in SDN Inpres Harapan.